REDESAIN ISTANA ANAK YATIM DARUL AZHAR DI TANAH BUMBU - Apriani, Helma; Aufa, Naimatul (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
Orphans receive special attention in the Al-Quran. The Al-Qurancommands Muslims to protect and nurture orphans. The effort of Muslims to fulfill this obligation is to provide a place to accommodate orphans so that they have the opportunity to live properly, obtain an education, and achieve their goals. In Tanah Bumbu Regency stands the Palace of Orphans under the auspices of the Darul Azhar Foundation. Judging from the National Standards of Parenting, the Palace of Orphans both in quantity and quality has not met the standard of facilities for a child social welfare institution. this condition has not been able to fulfill the vision and mission of the foundation to develop their potential and talents in the fields of art, sports, leadership, and religion. For this reason, a plan to redesign the Orphan Palace was initiated. This redesign was carried out using the infill design method. By initiating the concept of 'mutualism space' which means an old space or space with a new space or space that is mutually beneficial to one another, taking into account the interrelationship of functions and the interrelationship of needs between spaces. The new spaces that are present are analogous to facilities, functions, aesthetics, and other physical designs that are filled into an area that focuses on developing the potential of orphans. This concept and method are expected to be a solution to the problem of redesigning the Orphan Palace.